Identification of five novel MHC class II alleles in cynomolgus macaques of Vietnamese origin. (8th July 2016) - Wang, W.; Lu, Y.‐E.; Zhuo, M.; Ling, F.
Abstract : We report here the identification of one Mafa‐DPA1 and four Mafa‐DQB1 novel alleles of Vietnamese cynomolgus macaques.